Trixie and Jinx - Koontz, Dean; Cleland, Janet (USA, 2010)
Golden retriever Trixie misses her best friend, wiener dog Jinx, when Jinx's family takes him on vacation...
Keywords: Animal - Dogs; Animal Story; Friendship; Juvenile Fiction